PENGARUH CORPORATE GOVERNANCE TERHADAP RESTATEMENT LAPORAN KEUANGAN - Sari Indah Oktanti Sembiring; Mega Metalia (Jurnal Akuntansi dan Keuangan (JAK), 2019)
Using independent variable institutional ownership, managerial ownership, independent commissioner, audit committee, and BIG4, this research wanted to see the influence of corporate governance to financial restatement. By using sample of financial report from 2015 until 2017, this research found that institutional ownership is significant but unaccordance with the analyzed hypothesis. And the other independent variable is not significant with financial restatement. This founding may happened because the sample used in this research was not separated between the restated company because of error correction and because of the changes in accounting method that happened because the changes in accounting standard.